Diversity of Primary Structures of the Carboxy-terminal Regions of Mammalian Fibrinogen Aα-Chains - Murakawa, Masahiro; Okamura, Takashi; Kamura, Takumi; Shibuya, Tsunefumi; Harada, Mine; Niho, Yoshiyuki (Thrombosis and Haemostasis, 1993)
The partial amino acid sequences of fibrinogen Aα-chains from five mammalian species have been inferred by means of the polymerase chain reaction (PCR). From the genomic DNA of the rhesus monkey, pig, dog, mouse and Syrian hamster, the DNA fragments coding for α-C domains in the Aα-chains were amplified and sequenced. In all species examined, four cysteine residues were always conserved at the homologous positions. The carboxy- and amino-terminal portions of the α-C domains showed a considerable homology among the species. However, the sizes of the middle portions, which corresponded to the internal repeat structures, showed an apparent variability because of several insertions and/or deletions. In the rhesus monkey, pig, mouse and Syrian hamster, 13 amino acid tandem repeats fundamentally similar to those in humans and the rat were identified. In the dog, however, tandem repeats were found to consist of 18 amino acids, suggesting an independent multiplication of the canine repeats. The sites of the α-chain cross-linking acceptor and α2-plasmin inhibitor cross-linking donor were not always evolutionally conserved. The arginyl-glycyl-aspartic acid (RGD) sequence was not found in the amplified region of either the rhesus monkey or the pig. In the canine α-C domain, two RGD sequences were identified at the homologous positions to both rat and human RGD S. In the Syrian hamster, a single RGD sequence was found at the same position to that of the rat. Triplication of the RGD sequences was seen in the murine fibrinogen α-C domain around the homologous site to the rat RGDS sequence. These findings are of some interest from the point of view of structure-function and evolutionary relationships in the mammalian fibrinogen Aα-chains.